Investigation of axial-flexural behaviour of concrete-encased concrete-filled steel tube slender beam–columns - Wu, Nuoxin (2024)
In recent years, concrete-encased concrete-filled steel tube (CECFST) columns have gained popularity in structural engineering. Research studies have shown that this novel type of composite columns exhibits superior strength, ductility, stiffness, and resistance to fire and corrosion property when compared to alternative types of steel-concrete composite columns. Considering the increasing use of slender columns in practice, this study investigated structural behaviour of CECFST slender beam–columns subjected to combined compression and bending. In this paper, six pin-ended CECFST slender specimens with different section configurations, load eccentricities and slenderness ratios were tested under eccentric load. Key test results consisted of buckling mode analysis, load–deformation history, moment–curvature relationship and strain response at various locations. Results generally showed that P-δ effect deteriorated structural behaviour of CECFST slender beam–columns and this unfavourable effect should be addressed properly in the appropriate design code for composite columns. In this regard, design approaches in European code and American specification were evaluated in aspects of N–M interaction curve, moment magnification factor and effective flexural stiffness (EI)eff. It was identified that both codes tend to overestimate (EI)eff, resulting in an unconservative second-order analysis. Moreover, a parametric analysis was conducted which showed (EI)eff correlates negatively to eccentricity and slenderness, but positively to steel tube size and concrete strength. However, these relationships were not reflected in the predicted (EI)eff according to European code and American specification.